Preliminary investigation into the use of Micro-CT scanning on impact damage to fabric, tissue and bone caused by both round and flat nosed bullets. Issue 2 (March 2020) - Newton, Jayne; Savage, Anne; Coupar, Neil; Fraser, Joanna
Highlights: Penetration capability of 0.22 bullets into soft tissue and bone through clothing. Non-covered and covered gelatine blocks with and without bones to simulate a human. Different bullets used: Round nosed and flat nosed. CT scanning visualisation of internal and external damage caused by bullets. Level of damage caused to fabric, tissue and bone was affected by bullet type used. Abstract: Firearm offences in the UK, though not as high as in the USA, are increasing year upon year within both countries (Office for National Statistics, 2018 & Mervosh, 2018). This preliminary study looked into using Micro-CT scanning as a method to visualise impact damage and spray patterns caused by 12 test firings of both round and flat nosed bullets to porcine bone (shoulder and leg) suspended in ballistic gelatine and left with no covering, covered with a skin substitute, or covered with fabric (cotton or denim). Micro-CT scanning alongside VG Studio Max showed that overall, in the case of the shoulder bones the round nosed produced longer spray patterns (35.37 mm) within the gelatine blocks compared to the flat nosed bullet (27.33 mm); while with the leg bones the spray patterns were shorter, round nosed bullet (15.64 mm) and the flat nosed bullet (20.78 mm). These initial results showed that both bullet types produced considerable damage, from splitting to full penetration, which in turn illustrates how Micro-CT scanning has benefits within forensic ballistics, which should be further investigated.